Refractive Nonlinearity of Linear Symmetric Molecules and Polymers Revisited - Stegeman, George I.; Hu, Honghua (Photonics Letters of Poland, 2009)
In the paper a simple formula for the non-resonant and off-resonant nonlinearity in symmetric linear molecules and conjugated polymers made from such molecules is presented. Obtained results agree with experimental data known from the literature. Full Text: PDF References: Y. R. Shen, The Principles of Nonlinear Optics, Wiley Intersciences series (J. Wiley and Sons, New York, 1984) R. W. Boyd, Nonlinear Optics, (Academic Press), San Diego,(1992) C. Sauteret, J.P. Hermann, R. Frey, F. Pradere, J. Ducuing, R.H. Baughman, R.R. Chance, "Optical Nonlinearities in One-Dimensional-Conjugated Polymer Crystals", Phys. Rev. Lett., 36, 956 (1976).[CrossRef] Z. G. Soos, P. C. M. McWilliams and G. W. Hayden, "Coulomb correlations and two-photon spectra of conjugated polymers", Chem. Phys. Lett., 171, 14-18 (1990);[CrossRef] P. C. M. McWilliams, G. W. Hayden and Z. G. Soos, "Theory of even-parity states and two-photon spectra of conjugated polymers", Phys. Rev. B, 43, 9777-9791 (1991)[CrossRef] K. S. Mathis, M. G. Kuzyk, C. W. Dirk, A. Tan, S. Martinez and G. Gampos, "Mechanisms of the nonlinear optical properties of squaraine dyes in poly(methyl methacrylate) polymer", J. Opt. Soc. Am. B, 15, 871-883 (1998)[CrossRef] G. M. Carter, Y. J. Chen and S. K. Tripathy, Opt. Eng., 24, 609 (1985) J. Bolger, T. G. Harvey, W. Ji, A. K. Kar, S. Molyneux, B.S. Wherrett, D. Bloor, P. Norman, "Near-resonant third-order optical nonlinearities in p-toluene sulfonate polydiacetylene", J. Opt. Soc. Am. B, 9, 1552 (1992)[CrossRef] P. A. Gass, I. Abram, R. Raj, and M. Schott, "The nonlinear optical spectrum of polydiacetylene in the near infrared", J. Chem. Phys., 100, 88-97 (1994)[CrossRef] T. Kobayashi, "Ultrafast relaxation in conjugated polymers with large optical nonlinearitystar", Synth. Metals, 49-50, 565-581 (1992)[CrossRef] M. Samoc, A. Samoc and B. Luther-Davies, "Two-photon and one-photon resonant third-order nonlinear optical properties of ?-conjugated polymers", Synth. Met., 109, 79-83 (2000)[CrossRef] A. Bahtiar, K. Koynov, A. Kibrom, T. Ahn, and Chr. Bubeck, "Multiphoton spectroscopy of polymers for all-optical switching", Proc. of SPIE, 6330, 63300C-14 (2006)[CrossRef] D. W. Garvey, Q. Li, M. G. G. Kuzyk, C. W. Dirk and S. Martinez, "Sagnac interferometric intensity-dependent refractive-index measurements of polymer optical fiber", Opt. Lett., 21, 104-106 (1996)[CrossRef] S.-J. Chung et al, "Extended Squaraine Dyes with Large Two-Photon Absorption Cross-Sections", J. Am. Chem. Soc., 128, 14444-14445 (2006)[CrossRef] B. Lawrence, W. Torruellas, M. Cha, G. I. Stegeman, J. Meth, S. Etemad, and G. Baker, "Identification and Role of Two-Photon Excited States in a ?-Conjugated Polymer", Phys. Rev. Lett. 73, 597 (1994)[CrossRef] B. L. Lawrence, M. Cha, W. E. Torruellas, G. I. Stegeman, S. Etemad and G. Baker, "Measurement of the complex nonlinear refractive index of single crystal p-toluene sulfonate at 1064 nm", Appl. Phys. Lett., 64, 2773 (1994)[CrossRef] R. Quintero-Torres and M. Thakur, "Measurement of the nonlinear refractive index of polydiacetylene using Michelson interferometry and z-scan", J. Appl. Phy., 85, 401-3 (1999)[CrossRef] S. Polyakov, F. Yoshino, M. Liu, and G. Stegeman, "Nonlinear refraction and multiphoton absorption in polydiacetylenes from 1200 to 2200 nm", Phys. Rev. B 69, 115421-11 (2004)][CrossRef] M. Samoc, A. Samoc, B. Luther-Davies and M. Woodruff, "The concept of guiding light with light and negative third-order optical nonlinearities of organics", Pure and Applied Optics, 5, 681-7 (1996)[CrossRef] B. J. Orr and J. F. Ward, "Perturbation theory of the non-linear optical polarization of an isolated system", Mol. Phys., 20, 513-526 (1971)[CrossRef] M. G. Kuzyk and C. W. Dirk, "Effects of centrosymmetry on the nonresonant electronic third-order nonlinear optical susceptibility", Phys. Rev. A, 41, 5098-5109 (1990).[CrossRef] W. E. Torruellas, B. L. Lawrence, G. I. Stegeman and G. Baker, "Two-photon saturation in the band gap of a molecular quantum wire", Opt. Lett., 21,1777-9 (1996)[CrossRef] H. Hu, S. Webster, D. Hagan and E. W. Van Stryland, to be published C. W. Dirk, L.-T. Cheng and M. G. Kuzyk, "A simplified three-level model describing the molecular third-order nonlinear optical susceptibility", Int. J. Quant. Chem., 43, 27-36 (1992)[CrossRef]